Effectiveness of Sound-Based Interventions for Improving Functional Outcomes in Children: A Systematic Review of the Evidence - Vanessa Vincent; Gemma Skaczkowski; Donna Hughes-Barton; Kate M. Gunn (Occupational Therapy International)
Conclusions: There is preliminary evidence for the effectiveness of sound-based interventions in improving auditory sensitivity and emotional and behavioural outcomes. However, there is a need for higher quality studies, including randomised controlled trials, and consistency in outcomes across studies to enable a clearer assessment of the evidence.